A Search of the Full Six Years of the Dark Energy Survey for Outer Solar System Objects - Bernardinelli, Pedro H.; Bernstein, Gary M.; Sako, Masao; Yanny, Brian; Aguena, M.; Allam, S.; Andrade-Oliveira, F. [UNESP]; Bertin, E.; Brooks, D.; Buckley-Geer, E.; Burke, D. L.; Rosell, A. Carnero; et al. (American Astronomical Society, 2022)
We present a search for outer solar system objects in the 6 yr of data from the Dark Energy Survey (DES). The DES covered a contiguous 5000 deg2 of the southern sky with ≈80,000 3 deg2 exposures in the grizY filters between 2013 and 2019. This search yielded 812 trans-Neptunian objects (TNOs), one Centaur and one Oort cloud comet, 458 reported here for the first time. We present methodology that builds upon our previous search on the first 4 yr of data. All images were reprocessed with an optimized detection pipeline that leads to an average completeness gain of 0.47 mag per exposure, as well as improved transient catalog production and algorithms for linkage of detections into orbits. All objects were verified by visual inspection and by the sub-threshold significance,the signal-to-noise ratio in the stack of images in which its presence is indicated by the orbit, but no detection was reported. This yields a pure catalog complete to r ≈ 23.8 mag and distances 29 < d < 2500 au. The TNOs have minimum (median) of 7 (12) nights' detections and arcs of 1.1 (4.2) yr, and will have grizY magnitudes available in a further publication. We present software for simulating our observational biases for comparisons of models to our detections. Initial inferences demonstrating the catalog's statistical power are: the data are inconsistent with the CFEPS-L7 model for the classical Kuiper Belt; the 16 extremeTNOs (a > 150 au, q > 30 au) are consistent with the null hypothesis of azimuthal isotropy; and nonresonant TNOs with q > 38 au, a > 50 au show a significant tendency to be sunward of major mean-motion resonances.